Implikasi Tradisi Berhaji Bagi Masyarakat Sasak di Desa Sisik - Yuliani Yuliani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
The uniqueness of the Sasak community in preparing for the departure of prospective pilgrims to carry out the Hajj can attract the attention of researchers. So this research attempts to look at the traditions that the community carries out when carrying out the Hajj as well as the implications of the Hajj for the Sasak community. This study uses qualitative research using descriptive qualitative analysis by first collecting data through observations regarding what is happening in society, then conducting interviews. Documentation and individual experience to add data about Hajj. The results of this research show that the traditions before going on the pilgrimage for the Sasak people are still preserved today, because this tradition has existed since ancient times, from the time of our ancestors until now, it has been preserved from generation to generation. like tradition. Begawe, the opening of the pilgrimage, selararan and yasinan. The existence of this tradition has implications for the Sasak community, namely that the community has a stronger sense of solidarity, the community can build its social welfare. And for Hajj pilgrims it will be easy for them to return home.